PENERAPAN METODE FMEA DALAM MANAJEMEN RISIKO K3 UNTUK MENINGKATKAN PRODUKTIVITAS KERJA: STUDI KASUS DI PT. SURI TANI PEMUKA BANYUWANGI - Slamet Hariyadi; Muhammad Yusuf; Ainur Rofiq; Jusef Saiful (Yayasan Nusantara Hasana Berdikari, 2025)
Occupational Safety and Health (OHS) is an important aspect in industrial operations, especially in the fisheries sector which has high risks. This study focuses on the application of the Failure Mode and Effect Analysis (FMEA) method to identify and control work risks at PT. Suri Tani Pemuka Banyuwangi, with the aim of increasing work productivity. This study aims to analyze the effectiveness of the FMEA method in identifying risks and increasing work productivity at PT. Suri Tani Pemuka Banyuwangi. The research method used is a descriptive quantitative approach with a single case study design. Data were collected through observation, interviews, questionnaires, and documentation. The analysis was carried out by calculating the Risk Priority Number (RPN) based on the Severity, Occurrence, and Detection parameters to determine the priority of risk control. The results showed that the aerator machine maintenance activity had the highest RPN, which indicated a significant risk. The implementation of control measures such as the Lock-Out/Tag-Out (LOTO) procedure and OHS training succeeded in reducing work incidents by 58% and increasing harvest productivity by 15%. The conclusion of the research on the application of FMEA at PT. Suri Tani Pemuka Banyuwangi is effective in identifying and controlling work risks, as well as increasing productivity. This success is influenced by management commitment and active worker participation. Recommendations to develop a more integrated OHS management system with technology, such as the use of Smart PPE and data-based monitoring systems. Periodic evaluation of the risk control system is also important to ensure its effectiveness. Continuous training for workers and good collaboration between management and workers must continue to be improved to create a safe and productive work environment.